Modulating light level patterns reduces rest/activity disruption associated with shiftwork - Varun Mandi; Haley Miller; Jeongkyung Lee; Young-Hwa Goo; Mousumi Moulik; Ke Ma; Antoni Paul; Vijay K. Yechoor; Mariana G. Figueiro (npj Biological Timing and Sleep)
Abstract Long-term exposure to nonstandard work schedules can result in circadian misalignment, which has been linked to a series of maladies. To test whether modulating light patterns reduces shiftwork-induced rest/activity disruptions, 30 male C57BL/6 J mice individually housed in cages outfitted with running wheels were exposed to 6 simulated shiftwork light interventions. Mice experiencing high light levels during shiftwork exhibited a significant decrease in activity compared to low light levels during shiftwork and a conventional 12 L:12D condition, indicating circadian misalignment. In contrast, mice experiencing shiftwork in darkness combined with either modulated evening light pulses or circadian blind, vision-permissive light showed similar levels of rest/activity compared to a 12 L:12D condition, with phasor analysis indicating that their 24-h circadian rest/activity patterns were not misaligned. The results show that exposure to light that permits visibility but is below activation of the circadian system during shiftwork can prevent circadian misalignment.